The evolution of visual language in wine packaging - Pascual Cabrerizo, María; Martínez Lanzán, Gloria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Packaging plays a leading role in wine marketing: sight is the main sense that the buyer will use, so the relevance of visual language is almost as important as that of words in wine communication. This paper looks at the evolution of visual language in packaging through a literature review and the analysis of more than 500 samples. The results show a clear evolution in design towards originality, but also a shift from playing a basically persuasive role to being key in the identifying function and contributing to the informative function.